Sustaining Competitiveness: Promotional Mix Strategies in High-Performing Primary Schools Facing Demographic Shift - Eva Diana; Ahmad Rifandi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Declining student populations and increasing competition between public and private schools have required primary schools to adopt more strategic and structured marketing approaches. This qualitative multiple-case study analyzes how two high-performing primary schools in Margahayu District SD IT Anni’mah and SD Mathlaul Anwar design and implement promotion mix strategies within the New Student Admission System (SPMB). Data were collected through in-depth interviews, observations, and document analysis, and were examined using Miles and Huberman’s interactive data analysis framework. The findings reveal that the effectiveness of promotional strategies is closely linked to each school’s ability to integrate the elements of the marketing mix (7P). Program differentiation, transparent pricing, accessible school facilities, and a supportive physical environment significantly shape parental perceptions and enrollment decisions. A combination of online and offline promotional channels, including trial classes and targeted community outreach, proved effective in maintaining public interest. The professionalism of staff, clarity of communication, and well-organized administrative procedures further strengthened parent trust and contributed to a positive school image. Despite these strengths, both schools face challenges related to infrastructure limitations, digital content management, and staff development. However, their adaptive responses such as restructuring SPMB teams, improving digital materials, enhancing service clarity, and investing in teacher capacity-building demonstrate strong organizational resilience. This study contributes to the limited body of literature on educational marketing in primary schools by linking promotion mix implementation to demographic shifts and competitive pressures. It offers a structured understanding of how strategic, adaptive, and holistic promotional efforts enable high-performing schools to sustain their preferred status in an evolving educational landscape.